2020
DOI: 10.3390/sym12050755
|View full text |Cite
|
Sign up to set email alerts
|

Design Procedure of a Topologically Optimized Scooter Frame Part

Abstract: This article describes the design procedure of a topologically optimized scooter frame part. It is the rear heel of the frame, one of the four main parts of a scooter made with stainless steel 3D printing. The first part of the article deals with the design area definition and the determination of load cases for topology calculation. The second part describes the process of the topology optimization itself and the creation of the volume body based on the calculation results. Finally, the final control using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Furthermore, their paper discusses the problem of supplementing the code with the analysis of several load-cases, inserting passive areas, using filtering, etc. Another example of topology optimization procedures has been published by Jancar et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, their paper discusses the problem of supplementing the code with the analysis of several load-cases, inserting passive areas, using filtering, etc. Another example of topology optimization procedures has been published by Jancar et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the topology optimization is done to cut off the weight from the part, while ensuring that the part is functional and with comparable stiffness in comparison to its original counterpart. Specifically, in our study, we saved 63% of weight (From Figure Topological optimization has become a powerful area of study since such algorithms can be applied to many design problems in different physical disciplines, such as solid mechanics, fluid dynamics, and thermal dynamics [18][19][20]. By using topological optimization methods and related algorithms, a designer can generate innovative design ideas, especially in engineering fields.…”
Section: Topology Optimizationmentioning
confidence: 99%
“…The paper by Marsalek et al [10] demonstrated the capability of the SLS method for the production of flexible structures with complex geometries while using the PA12 (Polyamide 12) material. Other examples of printing complex geometries using TOP have been published by Jancar et al [11,12]. However, these papers use a different printing method, namely Selective laser melting (SLM)-a method that is similar to SLS, which, however, prints metal alloys and requires supports.…”
Section: Connecting Adaptermentioning
confidence: 99%